Punggung Sehat dengan Mckenzie Back Exercises Selama Pembelajaran Daring bagi Mahasiswa STIKes Hang Tuah Tanjungpinang - Yusnaini Siagian; Soni Hendra Sitindaon (Jurnal Abdimas Kesehatan (JAK), 2021)
Low back pain is pain that originates from the spine in the spinal area, muscles, nerves, tendons, joints, or cartilage due to the wrong position. Individuals who perform activities such as sitting up straight and bending over must be in the correct position. At Stikes Hang Tuah Tanjungpinang, a phenomenon was found that 42.7% of students complained of lower back pain due to wrong sitting habits such as sitting in a bent position when attending online lectures and doing college assignments. Sitting for too long in the wrong position causes muscle tension and spinal ligament strain. The results of interviews with students, most of the students who complain of low back pain do not understand what can be done to reduce or prevent low back pain due to sitting position and sitting too long. One of the non-pharmacological therapies to treat low back pain is McKenzie back exercises.  The purpose of this community service is to provide students with an understanding of low back pain and teach actions to reduce or prevent low back pain. The success indicator of this activity is that students understand and can perform the McKenzie back exercises The method used is to provide health education about low back pain and demonstrate McKenzie back exercises to students.